Integrating problem-based learning and augmented reality for enhancing problem-solving and computational thinking skills - Auliya, Risma Nurul; Sitthiworachart, Jirarat; Joy, Mike; Ratanaolarn, Thanin (My University, 2026)
The study investigated the effect of problem-based learning (PBL) with augmented reality (AR) on problem-solving and computational thinking (CT) skills, along with students’ satisfaction with AR in mathematics learning. Ninety eighth-grade students participated in a quasi-experiment with three groups: experimental (PBL with AR and standard PBL) and control (conventional learning) groups, each with thirty students. The geometry learning using augmented reality experience (GLARE) application covered 3D geometry, including cubes, cuboids, prisms, pyramids, cones, cylinders, and spheres. MANOVA was used to examine the problem-solving and CT skills, while the satisfaction was evaluated as percentages. The findings demonstrated all groups improved significantly in CT and problem-solving (p < 0.05), with the PBL+AR group achieving the highest improvement. Most students found AR engaging, motivating, and effective for understanding complex geometry concepts. They also appreciated its ease of use and support for independent learning. However, some encountered technical problems, such as device incompatibility and poor internet connectivity.
Keywords: augmented reality; computational thinking; PBL; problem-based learning; problem-solving; satisfaction